Concomitant solitary median maxillary central incisor and fused right mandibular incisor in primary dentition - G Shilpa; Sivakumar Nuvvula; Niraj Gokhale; V Yamini (Wolters Kluwer Medknow Publications, 2012)
Solitary median maxillary central incisor (SMMCI) is a unique developmental anomaly in primary dentition. It involves central incisor tooth germs and may or may not be associated with other anomalies. Its presence, concomitant with fusion of right mandibular incisors has not previously been reported. A 5-year-old girl was presented with a single symmetrical primary maxillary incisor at the midline, with the absence of labial frenulum, an indistinct philtrum and a prominent midpalatal ridge. There was an associated fused tooth in the right incisor region and radiographic examination confirmed only one maxillary central incisor in both the dentitions. Family history revealed that the father of the girl also had a similar anomaly providing probable evidence of etiological role for heredity in SMMCI.